Rhenium‐Doped and Stabilized MoS2 Atomic Layers with Basal‐Plane Catalytic Activity. Issue 51 (25th October 2018) - Yang, Shi‐Ze; Gong, Yongji; Manchanda, Priyanka; Zhang, Yu‐Yang; Ye, Gonglan; Chen, Shuangming; Song, Li; Pantelides, Sokrates T.; Ajayan, Pulickel M.; Chisholm, Matthew F.; Zhou, Wu
Abstract: The development of stable and efficient hydrogen evolution reaction (HER) catalysts is essential for the production of hydrogen as a clean energy resource. A combination of experiment and theory demonstrates that the normally inert basal planes of 2D layers of MoS2 can be made highly catalytically active for the HER when alloyed with rhenium (Re). The presence of Re at the ≈50% level converts the material to a stable distorted tetragonal (DT) structure that shows enhanced HER activity as compared to most of the MoS2 ‐based catalysts reported in the literature. More importantly, this new alloy catalyst shows much better stability over time and cycling than lithiated 1T‐MoS2 . Density functional theory calculations find that the role of Re is only to stabilize the DT structure, while catalysis occurs primarily in local Mo‐rich DT configurations, where the HER catalytic activity is very close to that in Pt. The study provides a new strategy to improve the overall HER performance of MoS2 ‐based materials via chemical doping. Abstract : Re‐doped MoS2 atomic layers in the distorted tetragonal structure show excellent activity and stability for electrocatalytic hydrogen production. Atomic‐level scanning transmission electron microscopy combined with density functional theory calculations reveal active local Mo‐rich structures and explain the best performance in Re0.55 Mo0.45 S2 . The study provides a new catalyst design strategy through chemical doping.